GUNNAR BENKTANDER 1919–2018. Issue 3 (8th August 2018) - Czapiewski, Colin; Dahl, Patrik; Havning, Mette; Mack, Thomas
Abstract : Gunnar Benktander passed away on February 25, 2018 at the age of 99. He left his family, and also the actuarial (non-life) community, after a long and very full life.